Revisiting species delimitation within Reithrodontomys sumichrasti (Rodentia: Cricetidae) using molecular and ecological evidence - Arellano, Elizabeth; Almendra, Ana L.; Martínez-Borrego, Daily; González-Cózatl, Francisco X.; Rogers, Duke S. (THERYA, 2023)
Reithrodontomys sumichrasti is distributed from central México to Panama. Previous studies using DNA sequences suggest the existence of distinct clades that may deserve species-level recognition. Here, we use multiple methods of species delimitation to evaluate if this taxon is a complex of cryptic species. DNA sequences from the genes Cyt-b, Fgb-I7, and Acp5 were obtained from GenBank to perform molecular analyses. Species boundaries were tested using the bGMYC, STACEY, and BPP species delimitation methods. Divergence times were estimated as well as the Cyt-b genetic distances. We developed Ecological Niche Models and tested hypotheses of niche conservatism. Finally, we estimated the spatiotemporal history of lineage dispersal. The bGMYC proposed two species while STACEY and BPP proposed 4 species (genetic distances ranged from 5.43 % to 7.52 %). The ancestral position of clade I was recovered, with a Pleistocene diversification time within R. sumichrasti at ~2.15 Ma. For clade pairwise niche comparisons, the niche identity hypothesis was rejected. The ancestral distribution of R. sumichrasti was centered in Central America and spread to the west crossing the Isthmus of Tehuantepec and extending to the mountain regions of Central México. Our taxonomic considerations included the recognition of four clades as distinct species within R. sumichrasti.